An overview of the survey of consumer expectations - Olivier Armantier; Giorgio Topa; Wilbert van der Klaauw; Basit Zafar (Federal Reserve Bank of New York, 2016)
This report presents an overview of the Survey of Consumer Expectations, a new monthly online survey of a rotating panel of household heads. The survey collects timely information on consumers' expectations and decisions on a broad variety of topics, including but not limited to inflation, household finance, the labor market, and the housing market. There are three main goals of the survey: (1) measuring consumer expectations at a high frequency, (2) understanding how these expectations are formed, and (3) investigating the link between expectations and behavior. This report discusses the origins of the survey, the questionnaire design, the implementation of the survey and the sample, and computation of various statistics that are released every month. We conclude with a discussion of how the results are disseminated, and how the (micro) data may be accessed.
Keywords: C81; D80; E31; 330; survey; expectations; inflation; measurement